Menstrual Pattern and Characteristics of One-Rod and Two-Rod Levonorgestrel Implant Users - Eka Rusdianto Gunardi; Sulaeman Andrianto Susilo (Hindawi Limited, 2021)
Introduction. The maternal mortality ratio (MMR) in Indonesia reaches 359 per 100,000 live births. The long-acting reversible contraceptive (LARC) method is an effective contraceptive choice for reducing MMR. The contraceptive implant is one of the LARCs that has low usage due to lack of education about the side effects. This study aims to compare the menstrual pattern and characteristics between one-rod and two-rod levonorgestrel implant users. Methods. A prospective cohort study was performed in patients at Cipto Mangunkusumo Hospital (RSCM) from March 2016 to May 2018. Subject recruitment was done by consecutive sampling. This study was conducted from March 2016 until May 2019. Statistical analysis was performed on the data using the chi-square test to determine the relationship between menstrual pattern and characteristics, and the use of one-rod or two-rod levonorgestrel implants. Results. A total of 140 subjects participated in the study, comprising 70 (50%) one-rod users and 70 (50%) two-rod users. In the first month, 32.9% one-rod users experienced amenorrhea, 22.9% experienced shortened menstrual period, 30% experienced normal menstrual period, and 14,2 % experienced lengthened menstrual period. In comparison, in the first month, 41.4% two-rod users experienced amenorrhea, 15.7% experienced shortened menstrual period, 32.9% experienced normal menstrual period, and 10% experienced lengthened menstrual period. There was no significant difference in menstrual patterns and characteristics between one-rod and two-rod levonorgestrel implant users. Conclusion. There was no significant difference in menstrual patterns and characteristics between one-rod and two-rod levonorgestrel implant users. Implications. Menstrual patterns and characteristics from levonorgestrel implants user can help clinicians to reduce discontinuation rate from the acceptors. Further research should be conducted to know other side effects aside from menstrual bleeding patterns.